Traveling the South Sea ... Of toponymy and historical cartography - Aguirre Lora, Georgina Maria Esther (Historia y Memoria de la Educación, 2020)
The purpose of this text is to approach an especially attractive territory, that of the Californias, which since its origins has been the setting for fascinating stories. These accounts have for the most part remained in the collective memory of the inhabitants of the region, constituting for them a source of pride and contributing to the imaginary inherent to the region’s name itself. The lore figures into the area’s changing cartographic expressions over the centuries, belying the fixed, static image suggested by the crystallized iconographic representations of successive maps as well as the changing names of the region,and their obliviousness to the stories contained in them. Thus, this text delves into the dimensions of historical cartography and toponymy to examinethe case of the Californias, an instance that we suggest be integrated into the learning of geographical knowledge.